Predictors of Indwelling Pleural Catheter Removal and Infection: A Single-center Experience With 336 Procedures. Issue 2 (April 2020) - Porcel, José M.; Torres, Magdalena; Pardina, Marina; Civit, Carmen; Salud, Antonieta; Bielsa, Silvia
Abstract : Background: Indwelling pleural catheters (IPCs) offer ambulatory management of symptomatic persistent pleural effusions, but their widespread use is somewhat hampered by the risk of pleural infection and the inconvenience of carrying a catheter for a prolonged period of time. Factors associated with these 2 limitations were analyzed in this study. Methods: Retrospective review of consecutive patients who had undergone IPC placement over a 5 ½-year period. Time to IPC removal was analyzed with the Fine and Gray competing risks survival model, with competing risk being death. A binary logistic regression method was used to evaluate factors influencing IPC-related pleural infections. Results: A total of 336 IPCs were placed in 308 patients, mostly because of malignant effusions (83%). IPC removal secondary to pleurodesis was achieved in 170 (51%) procedures at a median time of 52 days. Higher rates of IPC removal were associated with an Eastern Cooperative Oncology Group (ECOG) grade of 0 to 2 [subhazard ratio (SHR)=2.22], an expandable lung (SHR=1.93), and development of a multiseptated pleural space (SHR=1.37). IPC-related pleural infections occurred in 8% of the cases, and were more often seen in hepatic hydrothoraces [odds ratio (OR)=4.75] and pleural fluids with a C-reactive protein <15 mg/L before the IPC insertion (OR=4.42). Conclusion: IPC removal is more likely to occur in patients with good performance status whose lungs fully expand after drainage. Hepatic hydrothorax is the most significant predictor of IPC-related infections.